Disorder-induced Room Temperature Ferromagnetism in Glassy Chromites - Araujo, C. Moyses; Nagar, Sandeep; Ramzan, Muhammad; Shukla, R.; Jayakumar, O. D.; Tyagi, A. K.; Liu, Yi-Sheng; Chen, Jeng-Lung; Glans, Per-Anders; Chang, Chinglin; Blomqvist, Andreas; Lizárraga, Raquel; et al. (Scientific reports, 2014)
We report an unusual robust ferromagnetic order above room temperature upon amorphization of perovskite [YCrO 3 ] in pulsed laser deposited thin films. This is contrary to the usual expected formation of a spin glass magnetic state in the resulting disordered structure. To understand the underlying physics of this phenomenon, we combine advanced spectroscopic techniques and first-principles calculations. We find that the observed order-disorder transformation is accompanied by an insulator-metal transition arising from a wide distribution of Cr-O-Cr bond angles and the consequent metallization through free carriers. Similar results also found in YbCrO 3 -films suggest that the observed phenomenon is more general and should, in principle, apply to a wider range of oxide systems. The ability to tailor ferromagnetic order above room temperature in oxide materials opens up many possibilities for novel technological applications of this counter intuitive effect.